Analisis Penyebab Pending Klaim JKN Rawat Inap Di RSU Holistic Tahun 2026 - Octa Setyani; Sinta Novratilova (LPPM STIKES Marendeng Majene, 2026)
Abstract. Pending claims in the BPJS Kesehatan program remain a major challenge in hospital claim submission processes. At RSU Holistic, 865 out of 5,671 inpatient claims submitted between July and December 2025 were classified as pending, primarily due to inaccurate diagnosis and procedure coding. This study aimed to analyze the causes of pending inpatient BPJS claims based on the Man, Method, Material, Machine, and Money (5M) factors. This study employed a descriptive qualitative approach. The research object consisted of inpatient claim files submitted from January to March 2026, while the research subjects were case-mix officers. The study population comprised all five case-mix officers, and all were included as the sample using the total sampling technique. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data presentation, conclusion drawing, and verification. The results showed an increasing trend in pending claims, from 20% in January to 25% in March. The Man factor was related to communication problems with attending physicians (DPJP) during the clarification of diagnoses and medical procedures. The Method factor indicated the absence of a specific Standard Operating Procedure (SOP) for BPJS claim submission. The Material factor was identified as the primary cause of pending claims due to incomplete supporting documents. The Machine factor was associated with disruptions in the Hospital Management Information System (SIMRS), INA-CBGs application, and V-Claim system caused by downtime or maintenance. The Money factor reflected the financial impact of delayed claim reimbursements on hospital operational management. In conclusion, the increasing trend of pending inpatient BPJS claims at RSU Holistic was influenced by the Man, Method, Material, Machine, and Money factors, with Material and Method identified as the dominant contributing factors. Hospitals are recommended to establish a specific SOP for BPJS claim submission, strengthen interdepartmental coordination, and ensure the completeness of supporting documents before claims are submitted